Disruption of Nrf2 Enhances the Upregulation of Nuclear Factor-kappaB Activity, Tumor Necrosis Factor-α, and Matrix Metalloproteinase-9 after Spinal Cord Injury in Mice - Lei Mao; Handong Wang; Liang Qiao; Xiaoliang Wang (Hindawi Limited, 2010)
Matrix metalloproteinase-9 (MMP-9) plays an important role in the acute periods of spinal cord injury (SCI), and its expression is related to the inflammation which could cause the disruption of the blood-spinal barrier (BBB). Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key transcription factor that plays a crucial role in cytoprotection against inflammation. The present study investigated the role of Nrf2 in upregulating of nuclear factor kappa B (NF-κB) activity, tumor necrosis factor-α (TNF-α), and MMP-9 after SCI. Wild-type Nrf2 (+/+) and Nrf2-deficient (Nrf (−/−)) mice were subjected to an SCI model induced by the application of vascular clips (force of 10 g) to the dura after a three-level T8-T10 laminectomy. We detected the wet/dry weight ratio of impaired spinal cord tissue, the activation of NF-κB, the mRNA and protein levels of TNF-α and MMP-9, and the enzyme activity of MMP-9. Nrf2 (−/−) mice were demonstrated to have more spinal cord edema, NF-κB activation, TNF-α production, and MMP-9 expression after SCI compared with the wild-type controls. The results suggest that Nrf2 may play an important role in limiting the upregulation of NF-κB activity, TNF-α, and MMP-9 in spinal cord after SCI.